1985
DOI: 10.18174/njas.v33i3.16843
|View full text |Cite
|
Sign up to set email alerts
|

Relative synthesis rate of individual muscle proteins: a new approach

Abstract: This paper describes the estimation of the relative synthesis rate of muscle proteins by means of a new approach. This approach is an obvious alternative for isolation procedures, with usually low protein recovery. Loss of protein material is avoided by taking advantage of separating the muscle proteins in a single step by SDS gel fil tration. As a consequence an overall impression of the relative synthesis rate of the main muscle proteins can be visualized. This can be useful in comparative studies describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…RNA and protein ratio called the RNA unit [ 58 ] and the protein synthesis per RNA unit has been defi ned as the "activity" of RNA [ 58 ] and shown as a stable indicator of protein synthesis or eff ectiveness of the translation process in cell in physiological conditions [ 61 , 108 ] . About 4 decades ago, it was shown that the protein turnover rate depends on the type of muscle [ 28 ] and even functionally related proteins such as myofi brillar proteins have diff erent speed of renewal [ 79 ] . It was shown that a relationship exists between the turnover rate of myofi brillar protein and quantity of mitochondria in muscle [ 28 , 98 ] .…”
Section: Protein Synthesis and Degradation In Muscle Fi Bresmentioning
confidence: 99%
“…RNA and protein ratio called the RNA unit [ 58 ] and the protein synthesis per RNA unit has been defi ned as the "activity" of RNA [ 58 ] and shown as a stable indicator of protein synthesis or eff ectiveness of the translation process in cell in physiological conditions [ 61 , 108 ] . About 4 decades ago, it was shown that the protein turnover rate depends on the type of muscle [ 28 ] and even functionally related proteins such as myofi brillar proteins have diff erent speed of renewal [ 79 ] . It was shown that a relationship exists between the turnover rate of myofi brillar protein and quantity of mitochondria in muscle [ 28 , 98 ] .…”
Section: Protein Synthesis and Degradation In Muscle Fi Bresmentioning
confidence: 99%
“…Turnover Rate of MHC. The relative specific activity, which characterizes the turnover rate of MHC protein fraction, was calculated as the ratio of the specific activity of the protein fraction (Sb) to the specific activity of total muscle-cell protein (Sa; Schreurs, Boekholt, Koopmanschap, & van Rotterdam, 1985;Schreurs, Boekholt, & Koopmanschap, 1981) and expressed in percentages.…”
Section: Separation Of Total Muscle Cell Myofibrillar and Sarcoplasmentioning
confidence: 99%
“…After four hours the animal was killed and tissues were weighed and sampled. The specific activity (SA) of total tissue protein and individual muscle proteins was ex amined in protein fractions obtained by SDS gel filtration (Schreurs et al, 1983(Schreurs et al, , 1985.…”
Section: Methodsmentioning
confidence: 99%